Supe: la novela trunca de Arguedas - Dammert, Juan Luis (2011)
It had several names, «Harina Mundo», «Mar de Harina», «Jonás», «El pez grande», and was a literary project that José María Arguedas started after the publication of Todas las  Sangres (1964). The novel was intended to tell the story of ‘the transformations of Puerto Supe’, a fishing town he knew well, for he spent there the summer of 1943 and 1963. As we know, Arguedas later transformed this project into his last novel called El zorro de Arriba y el zorro de Abajo, which took place in the port of Chimbote.Two chapters of the unfinished novel about Supe were published while Arguedas was still alive: «Mar de Harina» and «El Pelón». In this article I present information about those chapters and the characters they portray, given that they were taken from real life. For this purpose, I draw on oral sources, such as my personal memories and the conversations I held in 2004 with the current inhabitants of Supe, about the characters of this unfinished project.